n-dimensional PDM non-linear oscillators: linearizability and Euler-Lagrange or Newtonian invariance - Mustafa, Omar (Iop Publishing Ltd, 2020)
We argue that, under multidimensional position-dependent mass (PDM) settings, the Euler-Lagrange textbook invariance falls short and turned out to be vividly incomplete and/or insecure for a set of PDM-Lagrangians. We show that the transition from Euler-Lagrange component presentation to Newtonian vector presentation is necessary and vital to guarantee invariance. The totality of the Newtonian vector equations of motion is shown to be more comprehensive and instructive than the Euler-Lagrange component equations of motion (they do not run into conflict with each other though). We have successfully used the Newtonian invariance amendment, along with some nonlocal space-time point transformation recipe, to linearize Euler-Lagrange equations and extract exact solutions for a set of n-dimensional nonlinear PDM-oscillators. They are, Mathews-Lakshmanan type-I PDM-oscillators, power-law type-I PDM-oscillators, the Mathews-Lakshmanan type-II PDM-oscillators, the power-law type-II PDM-oscillators, and some nonlinear shifted Mathews-Lakshmanan type-I PDM-oscillators.
Keywords: n-dimensional position-dependent mass Lagrangians; nonlocal point transformation; Euler-Lagrange equations invariance; Newtonian invariance amendment; linearizability and exact solvability of PDM nonlinear Euler-Lagrange oscillators' equations